2013
DOI: 10.1111/gcb.12217
|View full text |Cite
|
Sign up to set email alerts
|

Rapid warming accelerates tree growth decline in semi‐arid forests of Inner Asia

Abstract: Forests around the world are subject to risk of high rates of tree growth decline and increased tree mortality from combinations of climate warming and drought, notably in semi-arid settings. Here, we assess how climate warming has affected tree growth in one of the world's most extensive zones of semi-arid forests, in Inner Asia, a region where lack of data limits our understanding of how climate change may impact forests. We show that pervasive tree growth declines since 1994 in Inner Asia have been confined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
184
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 342 publications
(201 citation statements)
references
References 38 publications
8
184
0
Order By: Relevance
“…For example, 20th century warming caused shrub expansion ("arctic greening") in northern Siberia (Sturm et al 2001;Frost and Epstein 2014), whereas forest cover was reduced in central Yakutia from 1982 to 2005 due to permafrost degradation (Lloyd et al 2011). In the semi-arid forests of inner Asia, tree growth has declined since 1994 due to a temperature-induced reduction in effective moisture (Liu et al 2013). However, an increase in vegetation cover occurred between 1991 and 2000 on the Loess Plateau, especially in hilly regions (belonging to the semi-arid region), mainly as a result of ecological restoration (Sun et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, 20th century warming caused shrub expansion ("arctic greening") in northern Siberia (Sturm et al 2001;Frost and Epstein 2014), whereas forest cover was reduced in central Yakutia from 1982 to 2005 due to permafrost degradation (Lloyd et al 2011). In the semi-arid forests of inner Asia, tree growth has declined since 1994 due to a temperature-induced reduction in effective moisture (Liu et al 2013). However, an increase in vegetation cover occurred between 1991 and 2000 on the Loess Plateau, especially in hilly regions (belonging to the semi-arid region), mainly as a result of ecological restoration (Sun et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Forests in the taiga receive generally more precipitation and thus have developed higher stand densities and are also home to more water-demanding dark taiga tree species like Abies sibirica and Pinus sibirica (Dulamsuren, 2004;Dulamsuren et al, 2010a). Reports of increased drought stress, reduced stemwood formation, reduced forest regeneration and increased tree mortality, especially in the Larix sibirica-dominated forest-steppe ecotones of inner Asia, support this conclusion (Dulamsuren et al, 2010a(Dulamsuren et al, , b, 2013Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that forests are subjected to an increasing risk of growth decline, canopy dieback, and mortality under warming-induced drought stress in semi-arid areas [3][4][5][6], but on the other hand, climate warming has increased tree growth and recruitment in cold biomes [7,8]. However, the climate-growth relationship seems to be more complex in humid and sub-humid mountainous areas [9][10][11], where forest dieback and mortality episodes have been also recorded [2].…”
Section: Introductionmentioning
confidence: 99%